Prediction of residual deformations in products manufactured by selective laser sintering - Garashchenko, Yaroslav; Poharskyi, Andrii; Fedorovich, Vladimir; Harashchenko, Olena; Malyniak, Andrii (Національний технічний університет "Харківський політехнічний інститут", 2025)
This study addresses the critical challenge of predicting residual deformations in industrial products manufactured using selective laser sintering (SLS) technology. Residual deformations represent one of the primary factors leading to geometric inaccuracies in SLS-produced parts, directly affecting their functional performance and dimensional precision. The research proposes and validates a novel hypothesis that existing prediction models developed for plastic injection molding can be effectively adapted for SLS applications through appropriate conversion factors. Given the absence of specialized tools for SLS deformation prediction in the current market, this approach leverages the mature capabilities of the SOLIDWORKS Plastics software as an alternative solution. The methodology involves creating finite element models of test components, specifying material properties similar to SLS powders, and simulating thermal conditions that mimic the SLS process. Through a comparative analysis of twelve distinct geometries, a significant correlation between predicted deformations and actual measured deformations was established. This coefficient enables reliable translation between simulation results and actual SLS outcomes. The findings demonstrate that technological compensating deformations can be effectively calculated and applied to original triangulation models, substantially reducing geometric deviations in final products.

Дослідження розглядає критичну проблему прогнозування залишкових деформацій у промислових виробах, виготовлених за допомогою технології селективного лазерного спікання (SLS). Залишкові деформації є одним з основних факторів, що призводять до геометричних неточностей у деталях, виготовлених за допомогою SLS, безпосередньо впливаючи на їх функціональні характеристики та точність розмірів. Дослідження пропонує та підтверджує нову гіпотезу про те, що існуючі моделі прогнозування, розроблені для лиття пластмас під тиском, можуть бути ефективно адаптовані для застосування SLS за допомогою відповідних коефіцієнтів перетворення. Враховуючи відсутність спеціалізованих інструментів для прогнозування деформації SLS на сучасному ринку, цей підхід використовує відомі можливості програмного забезпечення SOLIDWORKS Plastics як альтернативне рішення. Методологія включає створення моделей скінченних елементів тестових компонентів, визначення властивостей матеріалу, подібних до порошків SLS, та моделювання теплових умов, що імітують процес SLS. Завдяки порівняльному аналізу дванадцяти різних конструкцій виробів було встановлено значну кореляцію між прогнозованими деформаціями та фактично виміряними деформаціями.
Прогнозування залишкових деформацій виробів, виготовлених за допомогою селективного лазерного спікання
Keywords: technology planning; selective laser sintering; residual deformation; triangulation models; technological compensating deformations; технологічна підготовка; селективне лазерне спікання; залишкова деформація; моделі тріангуляції; технологічні компенсуючі деформації